Al morfem fi al-lughah al-arabiyyah wa al-lughah al-Indunisiyyah - Adriana, Iswah (Fakultas Adab and Humaniora, Universitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2018)
This article focuses on the comparison of morpheme in Arabic and Indonesian language by contractive approach. This research discusses the description of morpheme in both the arabic and Indonesian language; analyzes the similarities and differences between morphemes in arabic and Indonesian Language; and also prediction of problem arises in learning Arabic language especially in learning morpheme based on the similarities and differences on those languages. As an example, based on its existence in speech, there is al- khali morpheme in arabic language such as …….(tulisan arab) contains dhamir (tulisan arab), while in Indonesian morpheme, the morpheme is not found here. This case will cause students get difficulties in learning Arabic language—Penelitian dalam artikel ini memfokuskan pada perbandingan morfem dalam bahasa Arab dan bahasa Indonesia dengan pendekatan analisis kontrastif. Penelitian ini membahas tentang deskripsi dari morfem baik dalam bahasa Arab maupun bahasa Indonesia, mencari sisi persamaan dan perbedaan antara morfem dalam bahasa Arab dan bahasa Indonesia, serta prediksi masalah yang muncul dalam pembelajaran bahasa Arab khususnya dalam pembelajaran morfem dengan berdasarkan pada persamaan dan perbedaan morfem dalam dua bahasa tersebut. Sebagai contoh, berdasarkan keberadaannya dalam tuturan, dalam bahasa Arab ada jenis morfem al-khali (morfem kosong) seperti lafazh ضَرَبَ yang di dalamnya menyimpan dhamir هُوَ , sedangkan dalam bahasa Indonesia morfem tersebut tidak ditemukan. Hal ini akan menyebabkan siswa mengalami kesulitan dalam pembelajaran bahasa Arab..